2018
DOI: 10.1016/j.sjbs.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of adverse effects of heat stress on Vicia faba by exogenous application of magnesium

Abstract: The effects of magnesium (Mg) supplementation on the growth performance, oxidative damage, DNA damage, and photosynthetic pigment synthesis, as well as on the activity level of carbonic anhydrase (CA), ribulose-1,5-bisphosphate carboxylase (Rubisco), and antioxidant enzymes were studied in Vicia faba L. plants exposed to heat stress (HS) and non-heat-stress (non-HS) conditions. Seeds were grown in pots containing a 1:1 mixture of sand and peat, with Mg treatments. The treatments consisted of (i) 0 Mg and non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This change is related to the additional application of Mg combined with to the rapid absorption of the element by the leaves and its high mobility in the phloem [ 26 ]. This increased Mg concentration may improve growth parameters due to the important roles that Mg plays in plant metabolism, especially those related to chlorophyll biosynthesis, photosynthesis, and carbon assimilation, in addition to activating numerous key chloroplast enzymes [ 21 , 23 , 27 ]. Interestingly, in most cases, it is difficult to change the leaf concentration of macronutrients through foliar spraying [ 28 ]; however, even with the absence of effect on plant nutrition, additional supply of macroelements during periods of high need by plants, may have increased the plant metabolism [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change is related to the additional application of Mg combined with to the rapid absorption of the element by the leaves and its high mobility in the phloem [ 26 ]. This increased Mg concentration may improve growth parameters due to the important roles that Mg plays in plant metabolism, especially those related to chlorophyll biosynthesis, photosynthesis, and carbon assimilation, in addition to activating numerous key chloroplast enzymes [ 21 , 23 , 27 ]. Interestingly, in most cases, it is difficult to change the leaf concentration of macronutrients through foliar spraying [ 28 ]; however, even with the absence of effect on plant nutrition, additional supply of macroelements during periods of high need by plants, may have increased the plant metabolism [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported the beneficial effect of Mg spraying to relieve environmental stresses in crops, such as drought stress [ 29 ], heat stress [ 20 , 27 ], and soil acidity stress [ 54 ], and temperature [ 30 ] by improving the antioxidant metabolism and reducing the cell damages. During the drought stress, there is a reduction in the use of the energy captured in the photosynthesis reaction centers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by-products such as TM provide a sustainable alternative for supplying Mg for cropping systems [12]. Supplying Mg to maize may improve crop growth and yield because of the important roles of Mg in plant metabolism, especially in photosynthesis and the activation of numerous key chloroplast enzymes [22,44,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mg is fundamental for a series of enzymatic activities and the synthesis of some proteins (Marschner, 2011;Shaul, 2002). Recent studies have also revealed a role of Mg in relieving stress caused by adverse growth conditions, such as aluminum, Mn and Pb toxicity (Bose et al, 2011;Kong et al, 2020;Gransee & Führs, 2013;Shen et al, 2016), photooxidative damage (Cakmak & Kirkby, 2008;Hauer-Já kli & Trä nkner, 2019), and heat stress (Mengutay et al, 2013;Siddiqui et al, 2018).…”
Section: Thementioning
confidence: 99%